Home care services for elderly patients with chronic diseases: A narrative literature review - Haidar, Muhammad; Chayati, Nur (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Comprehensive and continuous health services are provided to individuals and families in their place of residence to improve, maintain, or restore health, increase independence, and minimize the impact of disease. In Indonesia, the number of elderly people is increasing. Health services for older people should be a priority, along with the increasing number of elderly people. In terms of health services, older people need help. In addition, the elderly are more susceptible to various diseases, including degenerative and chronic diseases. Purpose: To determine the description of home health services for elderly patients with chronic diseases. Method: This study searched the following bibliographic databases to identify potentially relevant documents: Scien Direct, Pubmed, and MDPI publications in 2020-2024. Findings from the studies were extracted and compiled, guided by the Joanna Briggs Institute (JBI). Literature review using the Scien Direct, Pubmed, and MDPI databases. Keywords: "Home Care, Home Care Service and Home Care Nursing". A total of 1,176 articles were obtained. The final result obtained six articles that met the review requirements Results: The results of the study show that home health services use more technology to help the elderly who are experiencing chronic diseases. Home care services for the elderly with chronic diseases can be further developed by conducting more focused research on specific chronic diseases using systematic literature reviews with a larger number of studies to see the latest trends in research on home care services for the elderly with chronic diseases. Conclusion: Based on the results of research on six analyzed references, it states that home care services currently use more technology to help the elderly who are experiencing chronic diseases, although not all of them do.